Spectroscopic and Thermodynamic Studies of Charge- Transfer Complexes Formation Between Cytosine, Uracil and Thymine With Electronic Accepters - Al-Thib, Anwar T M; Al-Alwi, Nisreen K M; Eliwe, Ali S (Al-Nahrain Journal of Science, 2013)
Charge-transfer complexes of 2, 3-dichloro-5, 6-dicyano-1, 4-benzo quinone (DDQ), 2, 3, 5, 6-tetrabromo-1, 4-benzoquinone (Bromanil) and iodine as electronic acceptors with cytosine, uracil and thymine as electronic donors were studies and their electronic spectra were recorded. In each case one charge–transfer (CT) band was observed and recorded. These spectroscopic investigation make in ethanol solvent at four different temperatures (20, 25, 30 and 35°C). The values of equilibrium constant (KCT), molar extinction coefficient (εCT (, absorption band energy of charge –transfer complexes (hνCT) and the dissociation energy of the charge- transfer complexes excited state (W) were calculated and studied with discussed. The ionization potential of the donors (IP) were calculated and discussed from the charge–transfer complex band lowest energy. Thermodynamic parameters i. e. change in standard free energy (ΔG°), change in standard entropy (ΔS°) and change in standard enthalpy (ΔH°) for all these CT complexes were also calculated and discussed.